Non-islet cell tumor hypoglycemia concurrent with acromegalic features: A case report and literature review - Wang, Xiaojing; Li, Naishi; Xie, Yi; Zhu, Liang; Li, Ji; Gu, Feng; Xiao, Xinhua (Frontiers in Surgery, 2022)
Background Non-islet cell tumor hypoglycemia (NICTH) is a rare cause of hypoglycemia due to the overproduction of high molecular weight insulin-like growth factor (big-IGF2), which activates the insulin receptor and subsequently caused hypoglycemia. But NICTH with acromegaly had rarely been reported. We firstly reported a rare case of NICTH concurrent with acromegalic facial features induced by a retroperitoneal hemangiopericytoma and reviewed similar cases in the literature. Case presentation A 30-year old man was admitted to hospital because of recurrent unconscious, which usually occurred in the late afternoon or early morning before supper or breakfast. On one unconscious occasion, his blood glucose was 2.4 mmol/L. His consciousness recovered rapidly with intravenous 50% glucose administration. Physical examination showed that he had coarse oily facial features with acne, prominent forehead and brow, broad nose, prominent nasolabial folds. At the time of hypoglycemia, suppressed serum insulin, GH and IGF-1 levels was found. Computed Tomography further revealed a large left retroperitoneal mass measuring 7.0 cm × 12.3 cm × 13.0 cm. He underwent complete surgical resection of the mass. Surgical pathology demonstrated a hemangiopericytoma and strong positive for IGF-2. He did not experience further episodes of hypoglycemia after the operation during the 2.5 years follow-up. Conclusions Fibrous origin is the most common tumor type for NICTH with acromegaly features. NICTH should be considered in non-diabetic patients who have recurrent hypoglycemia along with suppressed serum insulin and IGF-1 levels.